On the Persistence of UK Inflation: A Long-Range Dependence Approach - Guglielmo Maria Caporale; Luis A. Gil-Ala\~na; Tommaso Trani (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper examines the degree of persistence in UK inflation by applying long-memory methods to historical data that span the period from 1660 to 2016. Specifically, we use both parametric and non-parametric fractional integration techniques, that are more general than those based on the classical I(0) vs. I(1) dichotomy. Further, we carry out break tests to detect any shifts in the degree of persistence, and also run rolling-window and recursive regressions to investigate its evolution over time. On the whole, the evidence suggests that the degree of persistence of UK inflation has been relatively stable following the Bretton Woods period, despite the adoption of different monetary regimes. The estimation of an unobserved-components stochastic volatility model sheds further light on the issues of interest by showing that post-Bretton Woods changes in UK inflation are attributable to a fall in the volatility of permanent shocks.
Keywords: C14; C22; E31; 330; UK inflation; persistence; fractional integration